2019
DOI: 10.1007/s41669-019-0149-9
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Mirabegron Compared with Antimuscarinic Agents for the Treatment of Adults with Overactive Bladder in Colombia

Abstract: Objectives The aim of this study was to evaluate the cost effectiveness of mirabegron relative to two antimuscarinics, oxybutynin extended release (ER) and tolterodine ER, in patients with overactive bladder (OAB) from the perspective of a third-party payer in Colombia. Methods A Markov model simulated the therapeutic management, disease course, and complications in hypothetical cohorts of OAB patients over a 5-year period. The model predicted costs and three outcomes: quality-adjusted life-years (QALYs), mict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 60 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Studies demonstrate across numerous countries that mirabegron is cost effective compared to various anticholinergic therapies. Therefore, it is important to continue to monitor cost of mirabegron, as our study appears to demonstrate an increase over time in this US dataset 22–25 . Furthermore, introduction of industry sponsored events pertaining to OAB are prevalent internationally 26 .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Studies demonstrate across numerous countries that mirabegron is cost effective compared to various anticholinergic therapies. Therefore, it is important to continue to monitor cost of mirabegron, as our study appears to demonstrate an increase over time in this US dataset 22–25 . Furthermore, introduction of industry sponsored events pertaining to OAB are prevalent internationally 26 .…”
Section: Discussionmentioning
confidence: 80%
“…Therefore, it is important to continue to monitor cost of mirabegron, as our study appears to demonstrate an increase over time in this US dataset. [22][23][24][25] Furthermore, introduction of industry sponsored events pertaining to OAB are prevalent internationally. 26 Marketing and pharmaceutical company promotion of newer products may play into prescribing patterns, although our study is unable to investigate this further.…”
Section: Discussionmentioning
confidence: 99%
“…20 Another cost per QALY study of Colombian patients with overactive bladder used EQ-5D-3L states reported by Colombian patients using index values from another multicountry study. 21 EQ-5D-5L has been applied in a study of hemodialysis patients in Medellín using the levels on EQ-5D-5L values, but no index or EQ VAS values. 22 EQ-5D-5L has also been used with index values to investigate the health status of Colombian patients with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Model inputs used treatment differences versus placebo and assumed that patients reverted to their baseline disease severity after discontinuing treatment, therefore representing a conservative approach. Because anticholinergics for the treatment of OAB contribute to ACB, the BIM incorporated the real-world impact of ACB, which was modeled via increased HCRU (outpatient and emergency department visits), an approach used in other published OAB economic models [12,22,30]. The largest offsets upon addition of vibegron to the formulary were regarding ACB, owing to patients who may have previously received an anticholinergic for OAB now receiving vibegron, a β 3 -adrenergic agonist with no anticholinergic activity.…”
Section: Discussionmentioning
confidence: 99%